OP66 Motivation to quit smoking and changes in cigarette consumption, among smokers who use e-cigarettes, findings from the health survey for england. (2nd September 2017) - Fat, L Ng; Scholes, S; Mindell, JS
Abstract : Background: The majority of people who use e-cigarettes are dual users with tobacco cigarettes. E-cigarettes may aid smokers with their quit attempts and reduce cigarette consumption or reinforce nicotine addiction. This study explores the motivations for current and previous use of e-cigarettes, and whether use is associated with reporting lower or higher cigarette consumption than a year ago. It makes comparisons with other traditional nicotine delivery products (NDPs). Methods: This study uses a sample of current smokers aged 16+ (n=3, 039) from the nationally representative, cross-sectional Health Survey for England, HSE2013–2014, (HSE2015 data will be included when archived). Firstly, multinomial logistic regression models were conducted on the odds of a) Never use of e-cigarettes versus b) Current use of e-cigarettes c) Previous (not current) use of e-cigarettes, and key exposure included the intentions to quit smoking scale (No intention/Pre-contemplation/Contemplation/Preparation (within next 3 months)). Secondly multinomial logistic regression was carried out on the odds of reporting smoking a) the same number of cigarettes versus b) more c) fewer than a year ago. Models were repeated using never, current and previous use of other NDPs. All models adjusted for sex, age-group, highest qualification and cigarette consumption. Analyses were conducted using Stata. Results: 12% were current users, and 20% previous users of e-cigarettes. Compared with never use of e-cigarettes, no association was found with age and current use, while being younger was associated with previous use (45–54 v. 16–34 years, OR=0.68 [95%CI 0.46–0.79]). Conversely, current and previous users of NDPs were more likely to be older than never users of NDPs (45–54 years 2.07 [1.29–3.30]). Quit intentions had a dose response relationship with the odds of current e-cigarette use (e.g. Preparation versus No intention (3.14 [2.24–4.42]); for previous e-cigarette users the magnitude was smaller (1.39 [1.04–1.87]). However, 'Preparation' had stronger associations with other NDPs, for both current (8.93 [5.54–14.40]), and previous use (3.18 [2.47–4.09]). Being a current user of e-cigarettes (1.77 [1.36–3.20]) or other NDPs (1.72 [1.19–2.50]) increased the odds of reporting smoking fewer cigarettes than the previous year; previous use was not significant. E-cigarette use was not associated with reporting smoking more than the previous year, however current use of NDPs was (1.84 [1.13–3.01]). Conclusion: Current or previous e-cigarette use is unlikely to increase consumption of cigarettes compared with a year ago, but smokers who used them had weaker intentions to quit smoking than smokers who used other NDPs. Longitudinal research is needed to track changes in consumption involving duration of e-cigarette use to further verify findings.